MENATAP TUHAN DALAM HARMONI SATYAM, SIVAM, SUNDARAM: TELAAH FILOSOFIS ATAS METAFORA KOSMIK - Krishnanandayani, Jyothi Devi; Maheswari, Prasanthy Devi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Upanisad, one of the sacred literatures in Hindu philosophy that contains various natural metaphors to explain the concept of unthinkable and transcendental divinity. These natural metaphors become a bridge that allows humans to understand God as Satyam (truth), Sivam (goodness), and Sundaram (beauty). This research is motivated by an in-depth exploration of the Upanisad texts that describe the dimensions of divinity using elements of the universe, which dimensions are not only spiritual but also relevant in human life. The purpose of this study is to identify and analyze natural metaphors in the Upanisad by understanding how these metaphors describe the nature of God in three main aspects: truth, goodness, and beauty. This study uses a qualitative method with a hermeneutic approach to interpret the Upanisad texts contextually, accompanied by a philosophical analysis to understand the implications of natural symbolism on the concept of divinity. The results of the study show that natural metaphors are used to describe the elements of eternity, purity, and universality of God. The metaphor of nature in the Upanisad is not only an aesthetic expression, but also a profound philosophical medium to describe God as Satyam, Sivam, Sundaram. This symbolism strengthens the understanding that God is not only present in the spiritual dimension but also manifested in the harmony of the universe, so that it can inspire humans to live a life in harmony with divine principles. In addition, the results of this study are expected to be a reference for cross-disciplinary studies between philosophy, theology, and spiritual ecology, especially in linking the relationship between humans, nature, and God.